Electrophoretic Deposition on Nonconducting Substrates: A Demonstration of the Application to Microwave Devices - Vilarinho, Paula M.
Through the use of a sacrificial carbon layer, this work reports a method of performing electrophoretic deposition (EPD) of thick films on fully nonconducting substrates, overcoming the restricting requirement for EPD of a conducting or partially conducting substrate. As a proof of concept, the method was applied to the development of microwave-thick films on insulating alumina substrates. The key parameter to be controlled is the thickness of the sacrificial carbon layer; this is expected to be a general result for the application of the processing method. The method allows direct patterning of the structure and leads to the potential use of EPD in a far wider range of electronic applications (multilayer ceramic capacitors (MLCCs), low-temperature cofired ceramics (LTTCs), and biotech devices). Furthermore, in conjunction with work reported elsewhere, the development of specific BaNd2Ti5O14 (BNT) thick-film microwave dielectrics opens up a technology platform for a range of high-quality factor (Q) devices. More specifically, 100-mu m-thick BNT layers were achieved with a dielectric constant of 149 and Q of 1161 (10 GHz). These materials can now be integrated with tunable dielectrics or dielectrics on metal substrates to provide a platform for devices in the front end of communication systems and cellular base stations.